2021
DOI: 10.5194/egusphere-egu21-711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of floodplain forest sensitivity to drought

Abstract: <p>Floodplain forests are very complex, productive ecosystems, capable of storing huge amounts of soil carbon. With the increasing occurrence of extreme events, they are today among the most threatened ecosystems. Our study’s main goal was to assess the productivity of a floodplain forest located at Lanžhot in the Czech Republic from two perspectives: carbon uptake (using an eddy covariance method) and stem radius variations (using dendrometers). We aimed to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our conclusion that the effects of single drought years were buffered to some extent contrasts with the dramatic drought effects reported across European forests in 2018 that suffered widespread defoliation, xylem hydraulic failure and mortality (Buras et al, 2020; Schuldt et al, 2020) but is consistent with other floodplain forest studies. For instance, the exceptionally high gross primary production during the warm spring in 2018 was found to compensate for losses later that year due to drought in a Czech floodplain forest (Kowalska et al, 2020). Similarly, tree growth recovered within two years after the 1976 drought for all herein analyzed floodplain forest species, which was attributed to the drought buffering effect of water availability in floodplain forests (Heklau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our conclusion that the effects of single drought years were buffered to some extent contrasts with the dramatic drought effects reported across European forests in 2018 that suffered widespread defoliation, xylem hydraulic failure and mortality (Buras et al, 2020; Schuldt et al, 2020) but is consistent with other floodplain forest studies. For instance, the exceptionally high gross primary production during the warm spring in 2018 was found to compensate for losses later that year due to drought in a Czech floodplain forest (Kowalska et al, 2020). Similarly, tree growth recovered within two years after the 1976 drought for all herein analyzed floodplain forest species, which was attributed to the drought buffering effect of water availability in floodplain forests (Heklau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Floodplain forests rank among the most rapidly disappearing ecosystems due to land conversion and drainage (Leuschner & Ellenberg, 2017; Mikac et al, 2018) and novel climatic conditions – like prolonged droughts – may amplify this trend through changing the hydrological regimes on which these forests depend. For instance, sinking groundwater levels may increase tree growth sensitivity to drought and susceptibility to drought-induced dieback (Mikac et al, 2018; Skiadaresis, Schwarz, & Bauhus, 2019) and this might bring these forests, which are among the most dynamic, productive and diverse Central European habitats (Kowalska et al, 2020; Tockner & Stanford, 2002), closer to a tipping point. On the contrary, the higher water availability in floodplain forests may buffer drought effects to a certain extent as trees might have access to groundwater in addition to precipitation-derived moisture (Heklau, Jetschke, Bruelheide, Seidler, & Haider, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These can significantly reduce the stabilisation of soil organic matter (SOM) due to deteriorated aggregation, and subsequent mineralisation promoted by increased soil temperature and aeration (Balesdent et al 2000, Hamza andAnderson 2005). On the other hand, many studies showed that appropriate management practices, which include crop diversity, mulching, supply of organic matter and organic fertilisers to the soil (soil fertility management, cultivation of perennial crops), control of wind and water erosion, the application of soil conservation technologies, and application of biowastes increase the SOC stock in agricultural soils (Poeplau and Don 2015, Kowalska et al 2020, Ledo et al 2020, Valkama et al 2020, Seitz et al 2022.…”
mentioning
confidence: 99%